Risoluzione dispute e piattaforme decentralizzate - Battaglini, Raffaele (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2022)
The commercial need for fast and efficient justice, combined with the need to relieve the backlog of litigation in the courts, has led to the expansion of alternative dispute resolution tools such as arbitration and mediation. In addition, digital platforms and the rise of online transactions have fostered the development of online dispute resolution tools within the platforms themselves. With the spread of blockchain technology and the adoption of smart contracts, these trends have expanded, which has led economic actors to implement decentralised dispute resolution systems based on blockchain technology, smart contracts, tokens and human oracles. This paper, after a brief introduction of the technological concepts, describes the reasons that led to the emergence of decentralised dispute resolution systems and the three platforms that exist to date, highlighting their characteristics, advantages, disadvantages and legal validity, then presents thoughts on their reasons and purposes, as well as possible future developments.